The Effect of Self-Organized Learning Environment Implementation on Critical Thinking Skills and Digital Ethics: Systematic Literature Review - Dewi septia Ningrum; Sri Ngabekti; Novi Ratna Dewi; Dyah Rini Indriyanti (FKIP - Universitas Riau, 2026)
The purpose of this study was to examine the application of the Self-Organized Learning Environment (SOLE) model to the development of students' critical thinking skills and digital ethics. A literature search was conducted through two databases, namely Scopus and Google Scholar, for the period 2021–2026. The selection process followed the PRISMA protocol, with the identification of 37 articles, screening based on title and abstract (n=28), and feasibility assessment resulting in 9 articles meeting the inclusion criteria. Inclusion criteria included: peer-reviewed journal articles in Indonesian or English, focusing on the implementation of SOLE in formal education contexts, and containing empirical data related to learning outcomes. The findings in this study are: 1) SOLE improves critical thinking skills because students are trained to search for information independently, analyze problems, and find solutions through group discussions. 2) The implementation of SOLE improves digital ethics through the habit of using technology wisely, the ability to evaluate information, and the responsible use of digital media. 3) There is a strong relevance between critical thinking and digital ethics in the implementation of SOLE, because critical thinking skills help students sort information appropriately, thus supporting the formation of responsible and ethical digital behavior.